COUP‐TFII in pancreatic adenocarcinoma: Clinical implication for patient survival and tumor progression. Issue 7 (15th October 2013) - Polvani, Simone; Tarocchi, Mirko; Tempesti, Sara; Mello, Tommaso; Ceni, Elisabetta; Buccoliero, Francesca; D'Amico, Massimo; Boddi, Vieri; Farsi, Marco; Nesi, Silvia; Nesi, Gabriella; Milani, Stefano; et al.
<x xml:space="preserve">Abstract</x> Despite the accumulating knowledge of alterations in pancreatic cancer molecular pathways, no substantial improvements in the clinical prognosis have been made and this malignancy continues to be a leading cause of cancer death in the Western World. The orphan nuclear receptor COUP‐TFII is a regulator of a wide range of biological processes and it may exert a pro‐oncogenic role in cancer cells; interestingly, indirect evidences suggest that the receptor could be involved in pancreatic cancer. The aim of this study was to evaluate the expression of COUP‐TFII in human pancreatic tumors and to unveil its role in the regulation of pancreatic tumor growth. We evaluated COUP‐TFII expression by immunohistochemistry on primary samples. We analyzed the effect of the nuclear receptor silencing in human pancreatic cancer cells by means of shRNA expressing cell lines. We finally confirmed the in vitro results by in vivo experiments on nude mice. COUP‐TFII is expressed in 69% of tested primary samples and correlates with the N1 and M1 status and clinical stage; Kaplan–Meier and Cox regression analysis show that it may be an independent prognostic factor of worst outcome. In vitro silencing of COUP‐TFII reduces the cell growth and invasiveness and it strongly inhibits angiogenesis, an effect mediated by the regulation of VEGF‐C. In nude mice, COUP‐TFII silencing reduces tumor growth by 40%. Our results suggest that COUP‐TFII might be an important regulator of the behavior of pancreatic adenocarcinoma, thus representing a possible new target for pancreatic cancer therapy.